The Development of Accommodation and Food Service Industry to Support Tourism in Yogyakarta Special Region - Wahyu Hidayati (Magister Administrasi Publik, 2019)
Accommodation and Food Service is an industry that is unevenly distributed across Special Region of Yogyakarta (DIY) (especially Kulon Progo). This research aims to: 1) identify key industries with the potential to support tourism industry development, 2) identify the tourism development strategies and programs needed to support sccommodation and food service Industry. The research used secondary data, which were analyzed using Klassen Typology and LQ Analysis. Research results show that : 1) Sleman District and Yogyakarta City are the leaders in the development of accommodation and food service industries, while , Kulon Progo, Bantul, and Gunungkidul are laggards in that respect. LQ Analysis results indicated that Bantul and Yogyakarta regions are leaders in the accommodation and food service sector, while Gunungkidul is promising and Sleman has good prospects, but Kulon Progo is an underperformer in the sector; 2) the development of Accommodation and Food Service industry has high potential hence need government attention. This is reflected in the contribution which the setor makes toward local government economy in terms of value of economic activities and employment generation. During 2013-2017, the industry contributed 10.12% of GRDP on average, and employed 13.87% of total workforce on average in the same period.